Surfactant Protein D Is Associated With Severe Pediatric ARDS, Prolonged Ventilation, and Death in Children With Acute Respiratory Failure - Dahmer, Mary K. (Chest, 2020)
BACKGROUND: Elevated surfactant protein D (SP-D) is a relatively specific indicator of lung injury and is associated with both acute and chronic lung disease in adults and respiratory distress syndrome in premature infants. The relationship between plasma SP-D and lung injury in children with acute respiratory failure is unclear. RESEARCH QUESTION: Is plasma SP-D associated with lung injury or outcome in children with acute respiratory failure? STUDY DESIGN AND METHODS: This was a prospective cohort study in children 2 weeks to 17 years of age with acute respiratory failure who participated in the BALI multi-center study. Analyses were done using SP-D levels in plasma from the first sample taken on either the day of intubation or one of the following 2 days. SP-D level was measured by enzyme-linked immunosorbent assay. RESULTS: Plasma samples from 350 patients were used in the analysis; 233 had pediatric ARDS (PARDS). SP-D levels varied across primary diagnoses (P < .001). Elevated SP-D levels were associated with severe PARDS after adjusting for age, pediatric risk of mortality III (PRISM-III), and primary diagnosis (OR = 1.02; CI = 1.01-1.04; P = .011). Multivariable analyses also indicated that elevated SP-D levels were associated with death (OR = 1.02; CI = 1.01-1.04; P = .004), duration of mechanical ventilation (P = .012), PICU length of stay (P = .019), and highest oxygenation index (P = .040). SP-D levels also correlated with age (r(s) = 0.16, P = .002). INTERPRETATION: Elevated plasma SP-D levels are associated with severe PARDS and poor outcomes in children with acute respiratory failure. Future studies will determine whether SP-D can be used to predict the degree of lung injury or response to treatment and whether SP-D is useful in identifying PARDS endotypes.